Comparison of intensity-modulated radiotherapy vs 3-dimensional conformal radiotherapy for patients with non-metastatic esophageal squamous cell carcinoma receiving definitive concurrent chemoradiotherapy: A population-based propensity-score-matched analysis. Issue 22 (June 2018) - Li, Chia-Chin; Chen, Chih-Yi; Chien, Chun-Ru
Abstract : Abstract: Whether the survival outcome of patients with non-metastatic esophageal squamous cell carcinoma (NM-ESCC) receiving definitive concurrent chemoradiotherapy (CCRT) is better with intensity-modulated radiotherapy (IMRT) or with 3-dimensional conformal radiotherapy (3DCRT) has been debated in the literature. We designed this population-based propensity-score (PS)-matched analysis to address this question. We identified eligible patients diagnosed between 2008 and 2015 from the Taiwan Cancer Registry and constructed a PS-matched cohort (1:1 for IMRT vs 3DCRT) to balance observable potential confounders. We compared the hazard ratio (HR) of death between IMRT and 3DCRT during the entire follow-up period. We also evaluated freedom from local regional recurrence (FFLRR) and esophageal cancer-specific survival (ECSS). Sensitivity analyses (SA) were performed to examine the robustness of our findings. Our study population constituted 558 patients who were well balanced with regard to the measured covariables. The HR of death with IMRT compared to 3DCRT was 0.43 (95% confidence interval 0.35–0.52, P  < .001). The results remained significant for FFLRR and ECSS. In SA, our results remained significant when additional covariables were taken into consideration. The survival outcome of patients with NM-ESCC receiving CCRT might be better with IMRT vs 3DCRT. These study results should be interpreted with caution given some possible covariates lacking in the registry. Further studies are needed to clarify this issue.